2012
DOI: 10.1515/cog-2012-0004
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of the active transitive construction in English: A detailed case study

Abstract: In this study, we test a number of predictions concerning children's knowledge of the transitive Subject-Verb-Object (SVO) construction between two and three years on one child (Thomas) for whom we have densely collected data. The data show that the earliest SVO utterances reflect earlier use of those same verbs, and that verbs acquired before 2;7 show an earlier move towards adultlike levels of use in the SVO construction and in object argument complexity than later acquired verbs. There is not a close relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Finally, although recasts occur frequently for common errors (e.g., hit for *hitted ), some types of overgeneralization error would seem to be too infrequent for sufficient feedback opportunities to occur. For example, a recent dense-database study of the transitive causative construction (Theakston, Maslen, Lieven, & Tomasello, 2012) failed to find a single overgeneralization error of the type observed in Bowerman's (1988) diary study (* He giggled me, *She came it over there and * I'm just gonna fall this on her ). Indeed, Bowerman (1988: 92) characterizes un - prefixation errors as “one-time errors” for which “learners do not have repeated opportunities to observe the way other people express this particular meaning.” For these infrequent errors, the question is not so much how children retreat from the few errors that they produce, but how they generally avoid such errors, while maintaining the capacity to produce novel grammatical utterances using the same productive generalization.…”
mentioning
confidence: 99%
“…Finally, although recasts occur frequently for common errors (e.g., hit for *hitted ), some types of overgeneralization error would seem to be too infrequent for sufficient feedback opportunities to occur. For example, a recent dense-database study of the transitive causative construction (Theakston, Maslen, Lieven, & Tomasello, 2012) failed to find a single overgeneralization error of the type observed in Bowerman's (1988) diary study (* He giggled me, *She came it over there and * I'm just gonna fall this on her ). Indeed, Bowerman (1988: 92) characterizes un - prefixation errors as “one-time errors” for which “learners do not have repeated opportunities to observe the way other people express this particular meaning.” For these infrequent errors, the question is not so much how children retreat from the few errors that they produce, but how they generally avoid such errors, while maintaining the capacity to produce novel grammatical utterances using the same productive generalization.…”
mentioning
confidence: 99%
“…Thus, it will surely have a stronger explanatory power than any other approaches mentioned above. In the future, the cognitive approach's research will be complemented by experimental studies [11].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cameron-Faulkner, Lieven, and Tomasello (2003) found that only around 23% of all subject-predicates in English child-directed speech were intransitive (defined as utterances with both a subject and single lexical predicate with sub-categories transitive, intransitive & other). Similarly, Theakston, Maslen, Lieven, and Tomasello (2012) found that only around 14% of tokens of transitivity alternating verbs were intransitive. In contrast, Japanese children of a similar age are reported to hear between 52% and 66% intransitive verb uses, depending on exactly which verbs are included (e.g.…”
Section: Introductionmentioning
confidence: 93%